Heavy metals and metallothionein in vespertilionid bats foraging over aquatic habitats in the Czech Republic - Pikula, Jiri; Zukal, Jan; Adam, Vojtech; Bandouchova, Hana; Beklova, Miroslava; Hajkova, Pavlina; Horakova, Jana; Kizek, Rene; Valentikova, Lucie (Environmental toxicology and chemistry, 2010)
There has been growing interest in the study and conservation of bats throughout the world. Declines in their absolute numbers in recent decades are due, in part, to the fact that insectivorous bats may bioaccumulate toxic pollutants. The purpose of the present study was to quantify heavy metal concentrations in kidney, liver, and pectoral muscle samples in relation to metallothionein (MT) levels. In total, 106 bats belonging to 11 European species (i.e., Myotis myotis, Myotis daubentonii, Myotis brandtii, Myotis nattereri, Myotis emarginatus, Myotis mystacinus, Pipistrellus pipistrellus, Pipistrellus nathusii, Pipistrellus pygmaeus, Nyctalus noctulla, Eptesicus serotinus) were used for the study. The highest MT levels were found in Pipistrellus pipistrellus. High MT levels were also found in juvenile bats and aquatic-insect-foraging species. Cadmium was found only in the liver and kidney of Myotis myotis, except for a solitary finding in Pipistrellus pipistrellus. Myotis myotis juveniles had significantly higher liver and kidney Zn concentrations than adults. Interestingly, the liver Pb concentration was approximately two times higher in females than in males of Myotis myotis. The same gender difference was found for kidney Zn concentration in Pipistrellus pipistrellus. The present study confirms exposure of vespertilionid bats to toxic heavy metals (Pb, Cd) in the Czech Republic and provides data on the essential element Zn and the metal-binding protein MT in bats foraging over aquatic, aquatic and terrestrial, and terrestrial habitats.
Keywords: Muscles; játra; Metals, Heavy; svaly; Environmental Monitoring; ledviny; Female; Kidney; zvířata; Metallothionein; monitorování životního prostředí; těžké kovy; ženské pohlaví; Liver; Male; Water Pollutants, Chemical; Animals; metalothionein; mužské pohlaví; Chiroptera; chemické látky znečišťující vodu